Grain sorghum response and Palmer amaranth control with postemergence application of fluthiacet-methyl - Reddy, Seshadri S.; Stahlman, Phillip W.; Geier, Patrick W.; Bean, Brent W.; Dozier, Tim (My University, 2015)
Palmer amaranth is a problematic weed in grain sorghum production in central United States. Due to limited herbicide options available and ever increasing herbicide-resistant weed species, there is a demand for new mode-of-action herbicides for use in grain sorghum. Fluthiacet-methyl is a relatively new active ingredient that inhibits the enzyme protoporphyrinogen oxidase in target plants. Field studies were conducted at three sites in central United States in 2010 and 2011 to evaluate crop response and Palmer amaranth control with postemergence application of fluthiacet-methyl in grain sorghum. Treatments included fluthiacet-methyl at 4.8 and 7.2 g active ingredient (a.i.) haˉ¹ alone and tank-mixed with 2,4-D amine at 260 g acid equivalent (a.e.) haˉ¹ or atrazine at 840 g a.i. haˉ¹. Carfentrazone at 8.8 g a.i. haˉ¹, atrazine at 840 g haˉ¹, and a non-treated control were also included. Fluthiacet-methyl treatments caused 9–38% crop injury at 4 ± 1 days after treatment. Tank-mixing atrazine with fluthiacet-methyl seldom affected crop injury, while mixing 2,4-D with fluthiacet-methyl often reduced crop injury. Generally, injury caused by fluthiacet-methyl alone or in combination with atrazine or 2,4-D disappeared within 3 weeks after treatment. Grain yields were reduced in one trial, when 2,4-D mixed with 4.8 or 7.2 g haˉ¹ of fluthiacet-methyl caused 18% and 13% plant lodging and 24% and 14% grain yield loss, respectively. Across site-years, fluthiacet-methyl alone at 4.8 or 7.2 g haˉ¹ provided 55–95% control of Palmer amaranth. Greater Palmer amaranth control (≥75%) with fluthiacet-methyl alone was achieved when weeds were small or density was low at the time of spraying. Tank-mixing atrazine with fluthiacet-methyl increased Palmer amaranth control and sorghum yields considerably. Tank-mixing 2,4-D with fluthiacet-methyl also increased Palmer amaranth control, but to lesser extent and less consistently than with atrazine. Results indicated that fluthiacet-methyl has potential for use in grain sorghum to combat weeds resistant to acetolactase synthase-inhibitors, triazines, and synthetic auxin herbicides. Tank-mixing atrazine or 2,4-D with fluthiacet-methyl is desirable for effective Palmer amaranth control.
Keywords: Grain sorghum; Fluthiacet-methyl; Crop injury; Postemergence; PPO-inhibitor; Weed control